Virus-Mimicking Polymer Nanocomplexes Co-Assembling HCV E1E2 and Core Proteins with TLR 7/8 Agonist—Synthesis, Characterization, and In Vivo Activity - Thomas R. Fuerst; Alexander Marin; Sarah Jeong; Liudmila Kulakova; Raman Hlushko; Katrina Gorga; Eric A. Toth; Nevil J. Singh; Alexander K. Andrianov (Journal of Functional Biomaterials)
Hepatitis C virus (HCV) is a major public health concern, and the development of an effective HCV vaccine plays an important role in the effort to prevent new infections. Supramolecular co-assembly and co-presentation of the HCV envelope E1E2 heterodimer complex and core protein presents an attractive vaccine design strategy for achieving effective humoral and cellular immunity. With this objective, the two antigens were non-covalently assembled with an immunostimulant (TLR 7/8 agonist) into virus-mimicking polymer nanocomplexes (VMPNs) using a biodegradable synthetic polyphosphazene delivery vehicle. The resulting assemblies were characterized using dynamic light scattering and asymmetric flow field-flow fractionation methods and directly visualized in their vitrified state by cryogenic electron microscopy. The in vivo superiority of VMPNs over the individual components and an Alum-formulated vaccine manifests in higher neutralizing antibody titers, the promotion of a balanced IgG response, and the induction of a cellular immunity—CD4+ T cell responses to core proteins. The aqueous-based spontaneous co-assembly of antigens and immunopotentiating molecules enabled by a synthetic biodegradable carrier offers a simple and effective pathway to the development of polymer-based supramolecular nanovaccine systems.